2006
DOI: 10.1084/jem.20060269
|View full text |Cite
|
Sign up to set email alerts
|

An autosomal dominant major gene confers predisposition to pulmonary tuberculosis in adults

Abstract: The molecular basis of genetic predisposition to pulmonary tuberculosis in adults remains largely elusive. Few candidate genes have consistently been implicated in tuberculosis susceptibility, and no conclusive linkage was found in two previous genome-wide screens. We report here a genome-wide linkage study in a total sample of 96 Moroccan multiplex families, including 227 siblings with microbiologically and radiologically proven pulmonary tuberculosis. A genome-wide scan conducted in half the sample (48 famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 26 publications
4
65
1
3
Order By: Relevance
“…Their deficiency, functional defect or genetic polymorphism has been associated with altered susceptibility to mycobacteriosis (Taffik, 2001;Casanova & Abel, 2002;Phillips et al, 2002;Acevedo-Whitehouse et al, 2005;Bellamy, 2005;Okada & Shirakawa, 2005;Hill, 2006;Naik, 2006). The chromosome location of some of these genes has been elucidated (Cervino et al, 2002;Bellamy, 2005;Baghdadi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Their deficiency, functional defect or genetic polymorphism has been associated with altered susceptibility to mycobacteriosis (Taffik, 2001;Casanova & Abel, 2002;Phillips et al, 2002;Acevedo-Whitehouse et al, 2005;Bellamy, 2005;Okada & Shirakawa, 2005;Hill, 2006;Naik, 2006). The chromosome location of some of these genes has been elucidated (Cervino et al, 2002;Bellamy, 2005;Baghdadi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It taught us more about the impact of infections on the genome of human populations than about the genetic determinism of infectious diseases. In this regard, the work of my colleague Laurent Abel and his collaborators, first detecting major genes by segregation studies (142)(143)(144)(145)(146) and then mapping these genes for conditions such as schistosomiasis, leishmaniasis, leprosy, and tuberculosis, has bridged the gap between population-based and patient-based studies of infectious diseases (147)(148)(149)(150)(151)(152)(153)(154). Interestingly, the effect of most major genes decreases with age.…”
Section: Common Variants and Infectious Diseasesmentioning
confidence: 99%
“…Second, several primary immunodeficiency disorders are associated with susceptibility to mycobacteria in a Mendelian fashion attributable to rare single gene mutations with high penetrance [5]. Third, several genome-wide studies of susceptibility to TB have been performed with family-based linkage studies and have identified several promising chromosomal loci [16][17][18][19]. Fourth, candidate gene association studies, which evaluate whether common polymorphisms in candidate genes are associated with susceptibility to disease, suggest several loci that are associated with Tb susceptibility.…”
Section: Disease Mechanism 1: Macrophages Genetics and The Innate Imentioning
confidence: 99%